(untitled) (Global Journal of Human-Social Science, 2023)
The literary canon is a collection of works officially recognized for their excellence and cultural importance Its construction is a historical process that reflects the choices and values of commonly dominant groups As a result the canon often excludes works written by marginalized groups including women This erasure of female writers has influenced the development of the school curriculum and limited young people s exposure to these authors and their works In Brazil the literary canon is dominated by male writers with little representation of literary works authored by women This lack of representation directly affects education in the country limiting exposure to literature written by women This work addresses the influence of the patriarchal literary canon on the approach to literature written by women in school